Non-pharmachological therapy in decreasing blood pressure among pregnant women with preeclampsia: a literature review - Nur Oktavia Hidayati; Lia Sari; Mela Yulianti; Shafira Rizki Amalia; Feni Agustina; Lukman Haqim; Dinda Sari Agustina; Nabila Salsabila; Siti Nur Fatimah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Pregnancy in which the body of a pregnant woman undergoes physical changes, and psychological changes due to increased pregnancy hormones. Hormonal changes during pregnancy cause changes in the cardiovascular system with increased blood pressure in pregnant women and triggers preeclampsia in pregnancy. The purpose of the literature study was to identify several non-pharmacological therapies in reducing blood pressure in pregnant women with preeclampsia. The research method used is a literature study with a narrative review approach. Search data using databases such as PubMed, EBSCO, and Google Scholar. The keywords used were “hypertension”, “non-pharmachological therapies”, “preeclampsia”, “pregnancy”. There were 7 articles that discussed non-pharmacological therapy by means of aerobic exercise, foot massage, progressive muscle relaxation and breathing control techniques, autogenic training, hydrotherapy, mushroom diet, cognitive behavioral therapy. Non-pharmacological therapy by reducing blood pressure in preeclampsia in pregnant women affects systolic and diastolic blood pressure during the therapy program with a period of time and a relaxation phase. In addition, other therapies reduce arterial stiffness in pregnant women with chronic hypertension.